Frame technology applied in the domain of IT processes job control - Leyk, Jerzy (Technologia ramek zastosowana do sterowania procesami wykonawczymi IT, 2011)
The idea of frames as cognitive means in modeling real situations is known also in software engineering. Languages to create hierarchies of frames and apply them to efficiently produce outputs that are similar yet different have been developed since 1980s. The paper presents the concept of frames and classical frame language resources used in software development to create programs. On top of this Sriptor, a specific language based on the same concept is presented. Scriptor is a language to be applied in job control of IT processes rather than in using programming languages. It has been designed and implemented by the author.The similarities and differences are analyzed. The paper intends to demonstrate what frame approach is and how frame technology may be applied in other domains beyond the traditional software development
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 96-107
Keywords: frame technology; programming tools